ANALISIS FAKTOR INTERNAL DAN EKSTERNAL KESULITAN BELAJAR SISWA MADRASAH DALAM BELAJAR MATA PELAJARAN MATEMATIKA - M. Imamuddin, M. Imamuddin -; Isnaniah, Isnaniah; Annisa Aulia, Annisa Aulia; Zulmuqim, Zulmuqim; Nurdin, Syafruddin (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2020)
The learning difficulties refer to a group of difficulties which are manifested in the form of real difficulties in the proficiency and use of listening, conversing, reading, writing, reasoning, or abilities in the field of mathematics. The purpose of this study was to analyze factors the difficulties of madrasah students in learning mathematics with the research subjects being students of class VII MTs N I Bukittinggi. The instrument used was a questionnaire. The results showed that students' learning difficulties in mathematics in terms of internal factors was 22.83% which was included in the high enough category with details: the difficulty of physiological factors was 19.24% with quite low categories, psychological factors of 26.42% with quite high category. The difficulty of learning mathematics in terms of external factors is 23.94% which is included in the category of high enough with the details: student learning difficulties in mathematics in terms of school factors is 24.85% with a high category, family factors of 9.40 % with low category, and community factors amounted to 37.58% with quite high category.